The use of selective progestin receptor modulators (SPRMs) and more specifically ulipristal acetate in the practice of gynaecology. (1st June 2017) - Rozenberg, Serge; Praet, Julie; Pazzaglia, Eliza; Gilles, Christine; Manigart, Yannick; Vandromme, Jean
Abstract : This review discusses the development of selective progestin receptor modulators (SPRMs) for use in women's health and specifically the use of ulipristal acetate (UPA) as emergency contraception (EC) and as a treatment for symptomatic fibroids in women who want to preserve their fertility or avoid a hysterectomy. As an EC, UPA 30 mg should be recommended for women, within 102 h of unprotected intercourse. As a treatment of fibroids, UPA (5 mg daily dose) should be administered for periods of three months as a pre‐surgical strategy, reducing bleeding and fibroid size and facilitating surgery. A proportion of these patients may even avoid surgery. Future developments will demonstrate whether UPA can be used for other indications such as endometriosis and breast cancer prevention or treatment.